Splenic and pancreatic rupture. Early suppurated pseudocyst - Croci, Fabio; Trostchansky, José; Farcic, Antonio (Cirugía del Uruguay, 1985)
Authors describe a case of splenic and pancreatic rupture in an operation having been postponed due to splenic originated hemorrhage in two instances, where a suppurated pseudocyst developed at an early stage, interpreted prior to reoperation as a left subphrenic abscess. Noted is the not too frequent occurrence of this pathology and its most noticeable characteristics.